Pelatihan Pemanfaatan Teknologi dalam Penyusunan Bahan Ajar bagi Para Guru Bahasa Inggris SMK di Banyuwangi Jawa Timur - Gozali, Agus; Dewi, Dian Novita; Inayati, Dian; Adi, Sugeng Susilo (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2025)
The use of technology in learning is not only a necessity but also a requirement for creating more creative, critical, innovative, and communicative learning. The integration of AI in learning changes the paradigm of teachers from being instructors to facilitators, collaborators, mentors, coaches, guides, and learning companions who can train students to become independent and responsible learners. However, this is hindered by the imbalance in teachers' knowledge regarding the use of technology in developing teaching materials. This Community Service Activity aims to provide guidance on the use of technology in developing English language teaching materials for English teachers at vocational high schools in Banyuwangi Regency, East Java. Teachers will participate in a three-month program for the development of English teaching materials, which includes the stages of needs analysis, training, guidance, and evaluation of activities.